IMPACT OF BUDGET PARTICIPATION ON JOB SATISFACTION AND EMPLOYEE PERFORMANCE WITH JOB RELEVANT INFORMATION (JRI) AS AN INTERVENING VARIABLE - Suryadharma Sim; Wiwik Utami (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2018)
The purpose of this study was to examine the relationship between budget participation on job satisfaction and employee performance. This study also to find empirical evidence related to Job relevant information (JRI) as an intervening variable on the relationship between budget participation with job satisfaction and employee performance. The data was collected through questionnaires distributed to the superintendent and manager-level employees at PT. Jaya Readymix. The Respondents in this study are the superintendent and manager-level employees of PT. Jaya Readymix totaling 65 people. Data analysis in this study is a linear regression model. The results showed that (1) budget participation has positive significant effect on job satisfaction and employee performance, (2) job relevant information (JRI) was mediated on the relationship between budget participation and job satisfaction, but not for employee performance.